Infeksi Saluran Kemih Rekuren pada Anak Perempuan Usia 7 Tahun: Sebuah Laporan Kasus - Wigati, Lucky Indar; Suryati, Elvi (Medula, 2026)
Urinary tract infection (UTI) is one of the most common bacterial infections in children and represents a significant cause of morbidity, particularly among girls. UTIs occur due to the invasion of microorganisms into the urinary tract, triggering local and systemic inflammatory responses. Based on the anatomical location, UTIs are classified into upper and lower urinary tract infections, while according to disease course they are categorized as first episode, recurrent, or complicated UTIs. Recurrent UTIs in children require special attention because of their potential to cause long-term complications, including renal damage. This case report describes a 7-year-old girl presenting with recurrent dysuria accompanied by lower abdominal discomfort and a history of chronic constipation. Physical examination revealed suprapubic tenderness without costovertebral angle tenderness. Urinalysis demonstrated leukocyturia, mild hematuria, positive nitrite, and cloudy urine, while urine culture showed the growth of Escherichia coli at a concentration of 10⁵ CFU/mL. Imaging studies of the kidneys and urinary tract revealed no structural abnormalities. The diagnosis of recurrent UTI was established based on clinical history, physical findings, and supporting investigations. Management included empirical intravenous antibiotic therapy, supportive treatment, and non-pharmacological education focusing on adequate hydration, proper voiding habits, and personal hygiene. This case highlights the significant role of non-anatomical risk factors, such as chronic constipation and habitual urinary retention, in the development of recurrent UTIs in children. A comprehensive management approach addressing both acute infection and predisposing factors is essential to prevent recurrence and preserve long-term renal function.